2014
DOI: 10.1016/j.ijporl.2014.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic cervical thymus: A clinicopathological study of consecutive, unselected infant autopsies

Abstract: This study revealed that ECT is an essentially benign anomaly that occurs frequently during the development of the thymus, and may disappear over the first few years of life. These results suggest a conservative approach to the management of ECTs would be appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Other studies of ectopic thymic tissue in the neck of children have found variable incidence, ranging from 0.99% of cases to 33% of cases . The lowest prevalence of 0.99% cases was reported in an ultrasound screening study of over 37 000 children and found that the incidence of ectopic intrathyroidal thymic tissue was inversely correlated with age .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Other studies of ectopic thymic tissue in the neck of children have found variable incidence, ranging from 0.99% of cases to 33% of cases . The lowest prevalence of 0.99% cases was reported in an ultrasound screening study of over 37 000 children and found that the incidence of ectopic intrathyroidal thymic tissue was inversely correlated with age .…”
Section: Discussionmentioning
confidence: 91%
“…18 Other studies of ectopic thymic tissue in the neck of children have found variable incidence, ranging from 0.99% of cases to 33% of cases. 19,20 The lowest prevalence of 0.99% cases was reported in an ultrasound screening study of over 37 000 children and found that the incidence of ectopic intrathyroidal thymic tissue was inversely correlated with age. 20 The study reporting a high incidence (33%) for intrathyroidal thymic tissue was from an infant autopsy study looking at a small number of cases, and also noted that the size of these lesions decreased with age.…”
Section: Cytomorphological and Ancillary Study Findingsmentioning
confidence: 98%
“…ECT has been commonly reported in the pediatric literature, mostly at autopsy, and uncommonly presents as a neck mass [1,5,6]. Most of the time, the finding may be incidental, correlating with a period of maximum growth of the thymus, but only rarely in adults, as they involute.…”
Section: Discussionmentioning
confidence: 99%
“…The most common presentation is as a neck mass, frequently near the inferior pole of the thyroid gland. 6 Cervical thymic cysts can be challenging to diagnose and are difficult to distinguish from lymphatic malformations and branchial cleft cysts. 5 Histopathological analysis is necessary for definitive diagnosis.…”
Section: Discussionmentioning
confidence: 99%